The Impact of Altruistic Leadership and Academic Supervision on Teachers’ Performance: The Mediating Roles of Teachers’ Happiness and Trust in School Leaders - Masbirorotni Masbirorotni; Robin Pratama; Friscilla Wulan Tersta; Eddy Haryanto; Aprillizavivaryati Aprillizavivaryati; Haris Elwardiansyah; Wila Yurnita; Ruben Pandi Quitolbo (FKIP Universitas Lampung, 2026)
This study examines how altruistic leadership and academic supervision affect teacher performance, with teacher happiness and trust in school leaders serving as mediating variables. The study was conducted among senior high school teachers in Tanjung Jabung Barat Regency, Indonesia. A quantitative research design was employed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Data were collected from 134 teachers selected from a population of 385 teachers across 18 senior high schools. The findings showed that academic supervision significantly enhanced teacher happiness (β = 0.647, p < .001), while altruistic leadership positively affected both teacher happiness (β = 0.244, p = .013) and trust in school leaders (β = 0.517, p < .001). Teacher happiness was a significant predictor of teacher performance (β = 0.677, p < .001) and served as the primary mechanism through which leadership practices influenced performance outcomes. In contrast, altruistic leadership and trust in school leaders did not have significant direct effects on teacher performance. These findings suggest that leadership practices contribute to teacher performance primarily through enhancing teachers’ psychological well-being rather than through direct behavioral effects. The study highlights the importance of fostering teacher happiness as a strategic resource for improving teacher performance and strengthening school effectiveness. The results contribute to the educational leadership literature by providing evidence of the indirect pathways linking leadership practices, teacher well-being, and performance. Keywords: altruistic leadership, academic supervision, teacher happiness, trust in school leaders, teacher performance.